Studies on the growth of the marine microalga Dunaliella salina (Teodoresco) - Kumar, P Sunil; Dharmaraj, S (Indian Journal of Fisheries, 2011)
The present paper reports on the growth pattern of Dunaliella salina cells cultured in different salinities and also in stressed conditions on exposure to mutagens (UV and PEG). The cultures were maintained in different salinities viz., 20, 25, 30, 35, 40, 45 and 50 ppt for a period of two weeks in triplicates and the growth rate was monitored. The peak growth (14.29 lakhs) was observed in 35 ppt on eleventh day indicating the ideal salinity for the culture of this species. The cultures in mid-exponential growth phase were exposed to UV light for 30 and 60 minutes and PEG at four doses viz. 0.125, 0.25, 0.5 and 1 gm/ml. Poorest cell growth was observed for half an hour UV treated cultures (3.51 lakhs/ml). A proportionate decrease in cell count was noticed with increase in the concentration of PEG.